A Bulk Queueing System with Starting Failure and Repair, Multiple Vacation, Stand-by Server, Closedown and N-Policy: S. Karpagam, Govindan Ayyappan - Team, Support (Thai Journal of Mathematics, 2022)
In this investigation, single server bulk queueing system with is analyzed with server's starting failure and repair, stand-by server, multiple vacation, closedown and N-policy. Numerical results of the proposed model have been derived.